Green synthesis of hydroxyapatite from eggshells using orange peel (Citrus sinensis) as a template for bioceramic - Ikaningsih, Manty Aldilani; Hidayat, Wahyu; Piseno, Wirawan; Nurdini, Lulu; Karmiati, Besse Titing; Rahman, Arif; Gamara, Ba’adilla Akhista (Politeknik Negeri Lhokseumawe, 2026)
This study addresses the environmental challenge posed by chicken eggshell and orange peel waste by developing a sustainable green synthesis route for hydroxyapatite (HAp). This work aimed to synthesize hydroxyapatite from eggshell-derived calcium using orange peel (Citrus sinensis L.) extract as a natural template and to evaluate the effect of extract concentration on the structural and morphological characteristics of the resulting material. Hydroxyapatite was synthesized via a wet-chemical precipitation method under alkaline conditions using orange peel extract at concentrations of 0%, 10%, 20%, and 30%. X-ray diffraction analysis confirmed hydroxyapatite as the dominant crystalline phase in all samples, with crystallinity values of 100%, 99.55%, 95.6%, and 95.2% for extract concentrations of 0%, 10%, 20%, and 30%, respectively, indicating controlled reduction in crystallite size with increasing extract concentration. Scanning electron microscopy revealed a progressive reduction in particle size, decreased agglomeration, and enhanced surface porosity, while energy-dispersive X-ray spectroscopy confirmed consistent elemental composition and high purity. Among the investigated conditions, the use of 30% orange peel extract produced the most favorable overall characteristics, combining refined microstructure and controlled crystallinity.